A ESCUTA PSICANALÍTICA COMO UM CUIDADO PALIATIVO - OTTO, STEPHANIE CRISTIN (2022)
Death is an imperative for every human being, but the way subjects experience illness and death goes beyond the individual experience of finitude. Dying with comfort and 7 dignity, even with an incurable disease such as cancer, is part of the purpose of palliative care. Paliative care seeks to alleviate suffering and support the person and their family, considering their subjectivity, history, spirituality, family and social ties. This qualitative research sought to understand how subjects with severe cancer, without curative possibilities, experience their illness and what their needs are, within the scope of palliative care. Two women with metastatic cancer were interviewed. Participants were chosen for convenience. Margarida was heard during five meetings at her home and Rosa, only once, in the hospital. Psychoanalysis permeated the entire listening process. The analysis of the interviews was based on the contributions of Freud (1985-1938) and Lacan (1936-1965), which inaugurate knowledge about the determinations of somatic illness in psychic life and in the face of the possibility of getting sick from internal conflicts. The interviews were linked to psychoanalytic theory, based on Lacan's concept of Real, and the psychosomatic phenomenon. As a result, we discussed the illness in the lives of the interviewees, as well as their difficulty in giving meaning to their own suffering. No indexes were found that Palliative Care was performed with them, in the molds of theory and specialty. The comfort and care of the interviewees was provided only by the family members, and not by the health teams. It is concluded that psychoanalytic listening constitutes an important form of palliative care, since the results of the interviews demonstrated the importance of the participants talking about their subjective issues and about their life history in relation to their own illness. We consider that a qualified listening work is essential in health services that provide care to seriously ill people, since it opens space for psychic elaboration and suffering relief and the possibility of family care and of composing a multidisciplinary team.